Design and development of an intelligent biomechatronic tumor prosthesis - Kocaoglu, Sitki; Akdogan, Erhan (ELSEVIER, 2019)
Nowadays, bone cancer patients using expandable prostheses (EPs) have to go to the clinic frequently to determine the limb length and to perform the extension if necessary, as long as their age-based growth lasts. This situation brings along problems such as increased physician workload, the patient's exposure to radiation at each measurement, a larger rate of extension due to the long interval period between each extension and thus reducing patient comfort as well as making the daily life of the patient difficult. In this study, a biomechatronic tumor prosthesis which is able to determine the need for extension by means of its hardware and intelligent control structure was developed to eliminate the aforementioned problems. Mechanical analysis of the designed prosthesis has been performed in the simulation environment, the prototype of the prosthesis has been produced, wireless communication and control system have been created and the performance of the system has been tested on the experimental setup. Limb length discrepancies (LLDs) of 1 mm and above between the healthy limb and the limb with a prosthesis were able to be detected by the system, and prosthesis extension procedure was successfully performed against the maximum soft tissue resistance to be possibly encountered. (C) 2019 Nalecz Institute of Biocybernetics and Biomedical Engineering of the Polish Academy of Sciences. Published by Elsevier B.V. All rights reserved.
Keywords: Bone cancer; Expandable tumor prosthesis; Intelligent control; Biomechatronics; Implanted battery; Wearable sensor; EXPANDABLE ENDOPROSTHESIS; LEG; FORCES; REPLACEMENTS; MACHINE; SURGERY; TISSUES; GAIT; Engineering